(E)-2-(4-Benzyloxy-2-hydroxybenzylidene)-N-phenylhydrazinecarbothioamide - Nisha, K. (International Union of Crystallography, 2011)
The title compound, C(21)H(19)N(3)O(2)S, exists in the thione form. The configuration about the C=N bond is E. The hydrazinecarbothioamide unit adopts an almost planar arrangement, with maximum deviations of 0.016 (3) and −0.016 (2) Å for the two thiourea N atoms. An intramolecular O—H⋯N hydrogen bond occurs. Weak intermolecular N—H⋯S, C—H⋯O and C—H⋯π interactions are observed in the crystal structure.